Complex regional pain syndrome following immunisation. Issue 10 (1st August 2012) - Richards, Stephanie; Chalkiadis, George; Lakshman, Raman; Buttery, Jim P; Crawford, Nigel W
Abstract : Complex regional pain syndrome type 1 (CRPS-1) is a clinical syndrome that affects one or more extremities and is characterised by persistent pain disproportionate to any inciting event, and at least one sign of autonomic dysfunction in the affected limb(s). The pathogenesis of this syndrome is poorly understood, but its onset is often precipitated by a physical injury, such as minor trauma, fracture, infection or a surgical procedure. In the literature, there are reports of CRPS-1 following immunisation with rubella and hepatitis B vaccines. Here we present a case series of CRPS-1 following immunisation in adolescents, with either diphtheria-tetanus-acellular pertussis (1 case), or human papillomavirus vaccines (4 cases). Enhanced awareness of this syndrome and its potential to occur following immunisation in the paediatric population is vital to the prompt and effective management of this condition.